2008
DOI: 10.1590/s1678-77572008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation and performance of bioactive dental restorative materials in deciduous and young permanent teeth

Abstract: Objective:The aim of this study was to investigate the adaptation of different types of restorations towards deciduous and young permanent teeth.Materials and Methods:Class V cavities were prepared in deciduous and young permanent teeth and filled with different materials (a conventional glass-ionomer, a resin-modified glass-ionomer, a poly-acid-modified composite resin and a conventional composite resin). Specimens were aged in artificial saliva for 1, 6, 12 and 18 months, then examined by SEM.Results:The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
5
15
1
1
Order By: Relevance
“…A recent SEM study showed that fluoride-releasing restorative materials caused the formation of crystals at the interface with the tooth [21]. This is probably associated with fluoride release and can be taken as an indication of the bioactivity of the material.…”
Section: Discussionmentioning
confidence: 99%
“…A recent SEM study showed that fluoride-releasing restorative materials caused the formation of crystals at the interface with the tooth [21]. This is probably associated with fluoride release and can be taken as an indication of the bioactivity of the material.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study did not specifically examine for marginal gap closure, nor did it report or depict any closure of these artificial marginal gaps by the materials tested. Additionally, when examined by scanning electron microscopy (SEM), the marginal interfaces of glass ionomer, resin‐modified glass ionomer, polyacid‐modified composite resin (compomer), and resin composite restoratives (placed in cavity preparations in deciduous and early permanent teeth) also demonstrated the presence of various morphologies of crystalline deposits on the tooth interface . Nevertheless, that particular study also did not attempt to examine marginal gap closure, nor did it report or demonstrate any significant marginal closure by these materials.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gjorgievska et al 29 showed that marginal adaptation of RMGICs in deciduous teeth was slightly inferior to that in immature permanent ones. The RMGICs tended to cause cracks adjacent to the interfacial region, but not in the material itself.…”
Section: Discussionmentioning
confidence: 98%